FAKTOR-FAKTOR PENYEBAB DAN DAMPAK RENDAHNYA MINAT BACA BUKU TARUNA POLITEKNIK ILMU PELAYARAN MAKASSAR - Novianty Palayukan (PIP Makassar, 2020)
The writing titled â€œFaktor-Faktor Penyebab dan Dampak Rendahnya Minat Baca Buku Taruna Politeknik Ilmu Pelayaranâ€ describes about the low of reading interest on students at Makassar Merchant Marine Polytechnic. This writing aims to identify the factors cause the low of reading interest and their impacts on students at Merchant Marine Polytechnic. The writer does this research in Makassar Merchant Marine Polytechnic during August. In this writing, the writer uses descriptive method and qualitative approach in collecting data by observation, interview and library research. The data which are collected in the means of observation and information result from various sources of both litertures and informen are analyzed by qualitative analysis method. The result of this research shows some factors identified which cause the low of reading interest on students at Makassar Merchant Marine Polytechnic, they are : the usage of electronic media fluently on students, internal motivation from kids, tightly scheduled on campus, and the low of library service. The impacts of these cause the low of achievement in the class/study, some disease caused by electronics radiant, the lack of self confidence, creativity, and the capability of communication and socialization.